Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Role of Virtual Classrooms in Achieving Learning Satisfaction During COVID-19 for Students of Taiba University Co-Prof. Rofaydah Adnan Al-Ansary 2. Obstacles of Applying E-Training in the Training and Professional Development Centers in the Sultanate of Oman from the Point of View of the Trainers Mr. Sulaiman Khalaf Saeed Al-Makhashni , Dr. Jamilah Hamid 3. The effect of cooperative learning on improving the performance level of some sport skills for 11th eleventh grade students in Muscat Governorate Mr. Dawod Amerv Al-Defaye , Co-Prof. Mahfoodha Sulaiman Al-Kitani , Co-Prof. Naser Yasser Al-Rawahi 4. The level of Arabic language teachers’ ability to develop skills Critical speaking among high school students Prof. Mahmoud Helal Abdelkader 5. The Reality of Educational Supervision in the Schools of Ramallah and Al- Bireh Governorate from the School Principals Point of View Co-Prof. Ashraf Mohammad Abu Khayran , Mrs. Nancy Rimon Rantisi 6. The reality of inclusive government school principals exercising their supervisory role on the inclusive education program in the capital, Amman from their own point of view Dr. Yahya Ahmad Alqabali , Dr. Samy Sulyman Mahasees 7. The level of knowledge of the skills of teaching reading comprehension based on effective instruction for teachers of learning disabilities in Jeddah Mrs. Wafa Yahia Mobajar , Co-Prof. Reem Mahmoud Gharib 8. The level of Psychological Immunity among Secondary School Female Students in the Capital’s secretariat-Sana’a. Mrs. Afrah Qasem Yehia Al-Ammari , Co-Prof. Elham Abdullah Mohammed Al-Eryani